2011
DOI: 10.1007/s12350-010-9336-x
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue attenuation patterns in stress myocardial perfusion SPECT images: A comparison between supine and upright acquisition systems

Abstract: Upright SPECT-MPI acquisition is associated with a unique attenuation pattern which is vastly different than the supine position. Female gender strongly impacted this attenuation pattern, particularly obese women. Our study is the first to describe, in details, the attenuation patterns with upright imaging and is critical for the accurate interpretation of SPECT-MPI acquired with upright systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…A recent study demonstrated substantially increased contribution to inferior and lateral wall attenuation within women who were imaged upright (12). This study does not focus on the apical artifacts that are seen on our system.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study demonstrated substantially increased contribution to inferior and lateral wall attenuation within women who were imaged upright (12). This study does not focus on the apical artifacts that are seen on our system.…”
Section: Discussionmentioning
confidence: 98%
“…The defect was assigned a classification (anterior, inferior or lateral) based on the location of the segment of minimum activity. The detailed methodology used in this study was published elsewhere [6]. The “density” of an attenuation defect was considered to be the inverse of normalized cont statistics of photon activity; as the lower the normalized cont statistics in a defect was, the denser the attenuation.…”
Section: Methodsmentioning
confidence: 99%
“…However, attenuation patterns with upright imaging systems have not been described. We compared the attenuation patterns observed in upright vs. supine acquisition [6]. In this paper we further examined the association of the attenuation patterns seen in upright imaging with gender and body habitus.…”
Section: Introductionmentioning
confidence: 99%
“…Worden et al supported this Bsecond look strategy^by observing a significant higher rate cardiac death or myocardial infarction in patients with matched prone and supine test results compared to patients with normal scan results (6.3 vs. 2.3 %) [60]. However, there is the potential of marked different attenuation profiles in prone and supine imaging, since inferior attenuation defects are more prevalent in women undergoing upright imaging [61]. Finally, the incremental value of prone imaging is debated by Malkerneker et al who found no incremental value of prone imaging in combination with AC versus AC or prone imaging alone in the number of equivocal test results in 324 patients with a mixed pre-rest likelihood of CAD (8,11, and 18 %, respectively) [62].…”
Section: Prone Imagingmentioning
confidence: 99%